Mixed 3D–2D Perovskite Flexible Films for the Direct Detection of 5 MeV Protons. Issue 1 (27th November 2022) - Basiricò, Laura; Fratelli, Ilaria; Verdi, Matteo; Ciavatti, Andrea; Barba, Luisa; Cesarini, Olivia; Bais, Giorgio; Polentarutti, Maurizio; Chiari, Massimo; Fraboni, Beatrice
Abstract: This study reports on a novel, flexible, proton beam detector based on mixed 3D–2D perovskite films deposited by solution onto thin plastic foils. The 3D–2D mixture allows to obtain micrometer‐thick and highly uniform films that constitute the detector's active layer. The devices demonstrate excellent flexibility with stable electric transport properties down to a bending radius of 3.1 mm. The detector is characterized under a 5 MeV proton beam with fluxes in the range [4.5 × 10 5 – 1.4 × 10 9 ] H + cm −2 s −1, exhibiting a stable response to repetitive irradiation cycles with sensitivity up to (290 ± 40) nC Gy −1 mm −3 and a limit of detection down to (72±2) µGy s −1 . The detector radiation tolerance is also assessed up to a total of 1.7 × 10 12 protons impinging on the beam spot area, with a maximum variation of the detector's response of 14%. Abstract : The direct detection of 5 MeV protons by flexible devices based on 3D–2D mixed perovskite is reported here. The mixture allows to directly deposit onto polymeric foils micrometer‐thick and highly uniform films that constitute the detector's active layer. This sensor can detect the dose of absorbed protons producing an electrical output signal.